Quality of Life and Mental Health Status Among Cancer Patients With Metastatic Spinal Disease - Liu, Yaosheng; Cao, Xuyong; Zhao, Xiongwei; Shi, Xiaolin; Lei, Mingxing; Qin, Haifeng (Frontiers in Public Health, 2022)
This study aims to investigate quality of life and mental health status and further to identify relevant risk factors among advanced cancer patients with spine metastases. This study prospectively included and analyzed 103 advanced cancer patients with spine metastases. Patient’s basic information, lifestyles, comorbidities, tumor characteristics, therapeutic strategies, economic conditions, quality of life, anxiety, and depression were collected. Patient’s quality of life was assessed using the Functional Assessment of Cancer Therapy-General Scale (FACT-G), and anxiety and depression were evaluated using the Hospital Anxiety and Depression Scale (HADS). Subgroup analysis was performed based on different age groups and a multivariate analysis was performed to test the ability of 20 potential risk factors to predict quality of life, anxiety, and depression. The mean total FACT-G score was only 61.38±21.26. Of all included patients, 52.43% had skeptical or identified anxiety and 53.40% suffered from skeptical or identified depression. Patients had an age of 60 or more and less than 70 years had the lowest FACT-G score (54.91±19.22), highest HADS-anxiety score (10.25±4.22), and highest HADS-depression score (10.13±4.94). After adjusting all other potential risk factors, age was still significantly associated with quality of life (OR=0.57, 95%CI: 0.38–0.86, P＜0.01) and depression (OR=1.55, 95%CI: 1.00–2.42, P=0.05) and almost significantly associated with anxiety (OR=1.52, 95%CI: 0.94–2.43, P=0.08). Besides, preference to eating vegetables, time since knowing cancer diagnosis, surgical treatment at primary cancer, hormone endocrine therapy, and economic burden due to cancer treatments were found to be significantly associated with quality of life. Number of comorbidities and economic burden due to cancer treatments were significantly associated to anxiety. Advanced cancer patients with spine metastases patients suffer from poor quality of life and severe anxiety and depression, especially among patients with an age of 60 or more and less than 70 years. Early mental healthcare and effective measures should be conducted to advanced cancer patients with spine metastases, and more attention should be paid to take care of patients with an age of 60 or more and less than 70 years in terms of their quality of life and mental health status.